Estudio de métodos y tiempos para el mejoramiento de la línea de producción en la empresa Frutti Rico (2023)
This research project presents a study of the process of making yogurt in the company REFRECOS FRUTI RICO, in order to measure the efficiency of the process and the productivity of the workers correctly using the resources available to the company. As companies want to be more productive, they need to know when problems related to the production process can be solved. Time analysis is an activity that involves the technique of establishing a standard of allowable time to do a defined task, following a pre-established procedure.